Current trends in the preparation of Nanoparticles for drug delivery - Irshad Ul Haq Bhat; Zakia Khanam; A.H. Bhat (Springer, 2017)
The efficiency of a drug depends on target specificity and its solubility. The non-specificity of the drug molecules not only needs extra doses to treat diseases but also is associated with adverse drug reactions. Thus, newly engineered nanoparticles as a vector represent an exciting example which has shifted the paradigm from conventional therapies such as surgery, chemotherapy, and radiation to the novel drug delivery system. Among the nanocarriers developed so far, silica and gold nanoparticles have emerged as potential candidates who can deliver different drug molecules at target sites in a controllable and sustainable approach. In the present era, drugs released and delivered by engineered nanoparticles have attracted enough attention because of the prospects in cancer therapy, in particular, and in the treatment of other ailments. The fundamental properties of nanoparticles in drug loading, releasing, and biochemical competency can be altered by means of suitable conjugation with appropriate coatings or external magnetic fields. Therefore, this book chapter is focused on preparation, development, and application of very recently reported silica and gold nanoparticle system as a drug delivery cargo.